A multi-attribute utility decision support tool for a smart campus—UAE as a case study - Ahmed, Vian; Saboor, Sara; Ahmad, Norita; Ghaly, Megan (Frontiers in Built Environment, 2022)
The advancement in technologies has improved the living standard of the cities, where the educational sector acts as a sustaining factor for the developments in a society. Up recently, the integration of the sector with smart cities concept has experienced exponential growth of interest from researchers. Though various definitions of the concept ‘Smart Campus’ has been proposed, however, integration of the end users’ perception is always lacking in the concept. This study, therefore, intends to build on the theory to classify the most significant criteria that underpin ‘smart campus’ by considering the institute’s stakeholders’ perceptions. A multi-step methodological approach is adopted to develop the decision support tool that allows the decision makers to invest in the optimum solution to transform the traditional campus into a smart campus. The study initially looks into criteria and sub-criteria from the literature that defines Smart Campus. Secondly, a survey is conducted by targeting a sample of students, faculty, administrative staff, and IT support personnel from a leading institute in the region as a single case study. Thirdly, AHP analysis was performed among different stakeholders. The findings suggested that there exists a consensus among the perception of diverse group of participants who perceive Smart Security and Safety, – Campus Navigation and Adaptive Learning as the most important criteria and applications to transform the traditional campus into a smart campus. Finally, the decision support tool development on the Utility function model allows the decision makers i.e. Network Manager, IT Manager, Systems and Cloud Manager and Senior Managers from Finance department as the decision makers to make informed and strategic decision in terms of the optimum solution for the transformation of traditional campus into a Smart Campus